Modus Operandi Tindak Pidana Sodomi oleh Oknum Guru terhadap Anak Didik - Huntoyungo, Abdul Fahri; Badu, Lisnawaty W; Mamu, Karlin Z (PT. Meja Ilmiah Publikasi, 2025)
This study aims to analyze in depth the modus operandi of sodomy crimes committed by teachers against students in educational settings, particularly in Gorontalo City. The main issues raised are the strategies, patterns, and supporting factors that enable sexual crimes to be committed by educators, as well as effective prevention and handling measures. The research method used is empirical law with a qualitative approach, where data is collected through literature review, observation, and direct interviews with law enforcement officials, perpetrators, and relevant parties at the Class IIb Correctional Institution in Gorontalo City. The research findings reveal that the perpetrators' modus operandi is highly structured, beginning with grooming, gift-giving, psychological manipulation, and threats to keep the victims silent. The perpetrators exploit their position and trust as teachers to approach the victims, as well as the economic and psychological vulnerabilities of the students. Environmental, social, and psychological factors play a significant role in shaping the deviant behavior of the perpetrators, while the monitoring systems in schools and families remain weak. The impact of this crime is far-reaching, including psychological distress, academic decline, and social stigma toward the victims. This study emphasizes the importance of strengthening internal monitoring systems in schools, sexual education, professional ethics training for teachers, and collaboration between schools, families, and law enforcement agencies. Research recommendations include the development of a multidisciplinary prevention model and routine evaluations of child protection systems in educational settings.